(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Introduction: cervical cancer is the second most common cancer of women in Bangladesh. Information about the extent of any cancer is critical for treatment planning .For the management of cervical cancer clinical staging is the first and foremost task and disease stage is the single most important prognostic factor. Objective: To know the distribution of clinical stages of cervical cancer, to validate the revised 2018 FIGO staging system for cervical cancer with a particular focus on stage 1B and to know the differences in distribution of stages among two cohort groups. Methods: Retrospective analysis was conducted among two cohorts of cervical cancer patients. First group of cervical cancer patients underwent Examination Under Anesthesia (EUA) for clinical staging during December 2011 to July 2017 and second cohort was the same type of patients undergoing same procedure by different group of observer from August 2017 to June 2019. Chi square test was done to know the difference in stages between two groups. P value <0.05 was considered as significant difference. Results: In the first (8.12.11-1.7.17) cohort ( n—479) maximum ( 68.21%) patients were between 41 to 60 years old. Similarly in the second ( 2.8.17—30.6.19 ) cohort ( n—256) maximum ( 63.45%) patients were between 41 to 60 years of age. Significant difference observed in the measurement of the size of the tumour when it was 2.1 to 4 cm in size. ( p value-0.001) . Great difference observed in performing cystoscopy during EUA ( p value -0.001) between two cohorts. In the first cohort 27.39% and in 2nd cohort only 2.73% patients underwent cystoscopy. Differences also observed in diagnosing stage 11A, B and 4 A diseases. Conclusion : The 2018 FIGO staging system for cervical cancer is useful to distinguish stage 1B disease and it is very fruitful in taking decision regarding management. An important information obtained from this analysis is that great variation can occur in diagnosing stages of cervical cancer by different group of observer. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 87-92